2017
DOI: 10.1186/s40104-017-0168-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacillus subtilis and Bacillus licheniformis supplementation in diets with low- and high-protein content on ileal crude protein and amino acid digestibility and intestinal microbiota composition of growing pigs

Abstract: Background Bacillus spp. seem to be an alternative to antimicrobial growth promoters for improving animals’ health and performance. However, there is little information on the effect of Bacillus spp. in combination with different dietary crude protein (CP) levels on the ileal digestibility and microbiota composition. Therefore, the objective of this study was to determine the effect of Bacillus spp. supplementation to low- (LP) and high-protein diets (HP) on ileal CP and amino acid (AA) digestibility and intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 80 publications
(94 reference statements)
8
36
2
Order By: Relevance
“…In our study, we demonstrated that supplementation of antibiotics in the diet also had a negative effect on the richness and diversity of the fecal microbiota of piglets. It has been reported that the richness and evenness of the microbiota were decreased in the feces of pigs fed Bacillus species-based probiotics [16,26]. Similarly, 1 g/kg of B. licheniformis-fermented products also reduce the richness and evenness of the fecal microbiota in piglets in the present study.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In our study, we demonstrated that supplementation of antibiotics in the diet also had a negative effect on the richness and diversity of the fecal microbiota of piglets. It has been reported that the richness and evenness of the microbiota were decreased in the feces of pigs fed Bacillus species-based probiotics [16,26]. Similarly, 1 g/kg of B. licheniformis-fermented products also reduce the richness and evenness of the fecal microbiota in piglets in the present study.…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, no obvious negative effects on bacterial richness and evenness were observed in the fecal content of the group that was fed 4.5 g/kg of B. licheniformis-fermented products. The abundance of Lactobacillus species and Bifidobacterium species were increased in the feces of growing pigs fed Bacillus species-based probiotics [26]. A linear trend of Bacillus species-based probiotics supplementation on the number of Lactobacillus species was found [21].…”
Section: Discussionmentioning
confidence: 90%
“…The rumen microbiota has some special microbial species to help ruminants to degrade feeds. In this paper, the genus Prevotella showed a decrease in the high fiber diet, which is not consistent with the previous study in human and pigs [31]. Prevotella is largely responsible for much of the proteolytic activity within the rumen and is important for breaking down plant protein into usable nitrogen, which becomes accessible for other microbes within the rumen [32].…”
Section: Discussioncontrasting
confidence: 92%
“…For absolute quantification of the 16S rRNA gene copy numbers, internal standards were created using a pool sample (Kaewtapee et al, 2017). Standards were purified using the GeneJET PCR Purification Kit (Thermo Scientific, Schwerte, Germany) and fluorometrically quantified using the Synergy .…”
Section: Quantitative Real-time Polymerase Chain Reactionmentioning
confidence: 99%